(untitled) (Fiep Bulletin - online, 2024)
Introduction: Lymphatic drainage and elastic bandaging are therapeutic techniques that offer different benefits. Lymphatic drainage stimulates circulation and reduces swelling, while elastic bandaging helps stabilize and support muscles. Both approaches have been used successfully in therapeutic and aesthetic contexts. Objective: The aim of this study was to evaluate the pain and sensory process in puerperal women during post-operative cesarean section healing, using a combination of elastic bandaging and/or lymphatic drainage. Methods: Two patients were selected, Patient 1 and Patient 2, who had different complaints: edema and burning for Patient 1, and edema and sensitivity for Patient 2. The treatments applied were different, with Patient 1 receiving a combination of the two techniques (elastic bandage and lymphatic drainage), while Patient 2 received only lymphatic drainage. Results: Patient 1 showed an improvement on the pain scale from 7 to 0, while Patient 2 improved from 7 to 1. Patient 1 showed less sensitivity in the stoichiometer evaluation, but there was inflammation of the points. However, at the end of the treatment, the normal sensitivity of the area resumed. Patient 2 showed sensitivity in all sessions. Conclusion: The lymphatic drainage technique alone or combined with the application of X-shaped elastic bandages can be used efficiently to normalize the condition of post-cesarean women. It is recommended that more studies in this area be carried out with a larger sample size.